Облік кредиторської заборгованості - Голуб, Наталя Олександрівна; Голуб, Наталья Александровна; Holub, Natalia (My University, 2020)
UK: або послуги, які були отримані або поставлені, або на які були виставлені рахунки-фактури, або вони були формально узгоджені з постачальником». Визначено місце кредиторської заборгованості у діяльності підприємства. Повна та правдива інформації забезпечує прийняття управлінських рішень щодо кредиторської заборгованості на підприємстві. Особливе місце в кредиторський заборгованості займають численні розрахунки з постачальниками і підрядниками. Встановлено, наявність простроченої заборгованості може призвести до погіршення іміджу підприємства. Кредиторська заборгованість надає можливість підприємству тимчасово користуватися запозиченими коштами, але з іншого боку - зменшує показники платоспроможності і ліквідності. Ефективне управління кредиторською заборгованістю належить до необхідних умов успішної діяльності, оскільки воно створює передумови для швидкого зростання бізнесу і збільшення фінансових можливостей підприємства. RU: В статье рассмотрены кредиторской задолженности и ее составляющие. Кредиторская задолженность определяется, как «обязательства оплатить товары или услуги, которые были получены или поставлены, или на которые были выставлены счета-фактуры, либо они были формально согласованы с поставщиком». Определено место кредиторской задолженности в деятельности предприятия. Полная и правдивая информации обеспечивает принятие управленческих решений по кредиторской задолженности на предприятии. Особое место в кредиторской задолженности занимают многочисленные расчеты с поставщиками и подрядчиками. Установлено, наличие просроченной задолженности может привести к ухудшению имиджа предприятия. Кредиторская задолженность позволяет предприятию временно пользоваться заемными средствами, но с другой - уменьшает показатели платежеспособности и ликвидности. Эффективное управление кредиторской задолженностью относится к необходимым условиям успешной деятельности, поскольку оно создает предпосылки для быстрого роста бизнеса и увеличения финансовых возможностей предприятия. EN: Accounts payable and its components are discussed in the article. Accounts payable - this is a special part of the firm property, and it is the subject of mandatory legal relations between the company and its creditors. The new definition “obligations to pay for goods or services that were received, delivered, or for which invoices were issued, or they were formally agreed with the supplier” was proposed in the article as Accounts Payable. An important point in accounting is the classification of debt. In the scientific literature, various classification features of accounts payable are given. The place of accounts payable in the enterprise activities was determined. In the ongoing economic relations, the presence of debt is an objective phenomenon. Due to the limited financial resources, debt significantly affects the financial condition of the enterprise and the results of its activities. Economic activities of business entities associated with the use of funds in a continuous cycle. The structure of enterprise funds sources of a significant share is borrowed funds, namely payables. The acceleration of cash flow is one of the important ways to improve the financial situation of industrial entities. The lack of enterprises own working capital due to deficiencies in the organization of accounting and analysis of accounts payable. Accounting as an ordered system for summarizing information about the activities of the enterprise is based on continuous documentation of business operations taking place. Full and truthful information provides management decisions on accounts payable within the enterprise. Numerous settlements with suppliers and contractors occupy a special place in accounts payable. The presence of arrears can lead to a deterioration in the image of the enterprise that was established in the paper. Analyzing data on the status of accounts payable, it is necessary to study the causes of each type of debt, based on the specific production situation at the enterprise. Accounts payable allows the company to temporarily use borrowed funds, but on the other hand it reduces solvency and liquidity indicators. Effective accounts payable management is one of the necessary conditions for the successful activity since it creates the prerequisites for the rapid growth of the business and increase the financial capabilities of the enterprise, namely, it allows expanding markets for goods, attracting new sellers of products.
Accounts payable at the enterprise
Keywords: зобов’язання; кредиторська заборгованість; управління; боржник; позика; аналіз; оцінка; обязательства; кредиторская задолженность; управление; должник; заем; анализ; оценка; liabilities; accounts payable; management; debtor; loan; analysis; evaluation